Absorption Capability of a 645-nm Diode Laser on Swine Soft Tissue Samples: a Preliminary Study in an Ex-Vivo Model - Ghidini, Giulia; Vescovi, Paolo; Meleti, Marco; Giacomo, Setti; Alessandro, Sala; Roberto, Sala (UI Scholars Hub, 2019)
Most published articles have highlighted several positive effects of low-level laser therapy on tissues; however, to our knowledge, no studies have investigated the depth to which a light beam penetrates cell layers of an irradiated tissue. To date, it is unclear if the laser reaches cells and how many of the cells can be reached in the tissues underlying the oral mucosa. This is of paramount importance as the effect of a laser at a particular depth (e.g., the periosteum and/or bone) should be measurable and predictable to some extent Objectives: The present preliminary ex vivo study aimed to assess the possible interaction between complex biological systems and laser light through the irradiation of different soft tissue samples. Methods: A 645-nm wavelength diode laser was used for evaluation. Owing to known similarities with human tissues, swine tissue samples harvested from the mandibular oral mucosa were used. One sample of periosteum (0.45-mm thick), two mucosal samples (0.5- and 1-mm thick), and three samples, including both the mucosa and periosteum (1-, 1.3-, and 1.65-mm thick), were used as target soft tissues. Measurements were recorded with a power meter located under the irradiated tissues. Results: The mean absorption values for the 0.5-mm mucosa sample; 0.45-mm periosteum sample; 1-, 1.3-, and 1.65-mm mucosal and periosteum samples; and 1-mm mucosal sample were as follows: 70.64 ± 20.14 mW; 90.75 ± 42.87 mW; 93.40 ± 18.68 mW, 101.93 ± 13.60 mW, and 102.80 ± 18.54 mW; and 111.40 ± 13.22 mW, respectively. Conclusion: The red-light laser with a 645-nm wavelength can reach cells in each layer of the measured tissues.